Low intensity rowing with blood flow restriction over 5 weeks increases VO2max in elite rowers: A randomized controlled trial - Held, S.; Behringer, M.; Donath, L. (Journal of Science and Medicine in Sport, 2020)
The present randomized controlled intervention study examined the effects of practical blood flow restriction (pBFR) on maximal oxygen uptake (V O2max) during low intensity rowing. Design: Thirty-one elite rowers were either assigned to the intervention (INT) or control (CON) group, using the minimization method (Strata: Gender, Age, Height, V O2max). Method: While INT (n = 16; 4 female, 12 male, 21.9 ± 3.2 years, 180.4 ± 8.7 cm, 73.6 ± 10.9 kg, V O2max: 63.0 ± 7.9 ml/min/kg) used pBFR during boat- and indoor-rowing training, CON (n = 15, 4 female, 11 male, 21.7 ± 3.7 years, 180.7 ± 8.1 cm, 72.5 ± 12.1 kg, V O2max: 63.2 ± 8.5 ml/min/kg) completed the identical training without pBFR. pBFR of the lower limb was applied via customized elastic wraps. Training took place three times a week over 5 weeks (accumulated net pBFR: 60 min/week; occlusion per session: 2-times 10 min/session) and was used exclusively at low intensities (<2 mmol/L). A spiroergometric ramp test (V O2max; 30-40 W/min increase) on rowing-ergometer and one-repetition maximum test of the squat exercise (SQ1RM) was employed to assess endurance and strength capacity. Results: Significant group × time interactions ( p² = 0.26) in favor of INT were found for V O2max (+9.1 ± 6.2%, Effect Size = 1.3) compared to CON (+2.5 ± 6.1%, ES = 0.3). SQ1RM ( p² = 0.01) was not affected by the pBFR intervention. Conclusions: This study revealed that 15 sessions of pBFR application with a cumulative total pBFR load of 5 h over a 5 weeks macrocycle remarkably increased V O2max. Thus, pBFR might serve as a promising means to improve aerobic capacity in highly trained elite rowers.